Adverse Drug Reactions in Multimorbid Older People Exposed to Polypharmacy: Epidemiology and Prevention - Siobhán McGettigan; Denis Curtin; Denis O'Mahony (MDPI AG, 2024)
Adverse drug reactions (ADRs) are frequent and represent a significant healthcare burden. ADRs are a potentially avoidable contributor to excess unscheduled hospital admissions, higher morbidity, mortality, and healthcare costs. The objective of this review is to examine the epidemiology of ADRs in older multimorbid adults and to explore strategies for ADR prevention. ADRs in this population are often linked to commonly prescribed medications, including anticoagulants, antiplatelet agents, insulin, and non-steroidal anti-inflammatory drugs, but ADRs and adverse drug events (ADEs) in fact encompass a much broader range of culprit drugs. Age-related factors such as changes in pharmacokinetics and pharmacodynamics, multimorbidity, polypharmacy, and frailty have been associated with ADR occurrences. Various strategies have been proposed to prevent ADRs in different clinical settings, such as structured routine medication review and the use of bespoke software applications to identify potentially inappropriate prescriptions and drug interactions. Although these approaches have demonstrated some improvement in the quality of prescribing, there is still a lack of consistent evidence regarding their effectiveness in preventing ADRs. The nuanced and often intricate complexities associated with older patients' pharmacotherapy necessitate a comprehensive approach to attenuate the impact of ADRs within this growing section of most populations globally.